189k views
5 votes
Please help photo attached

Please help photo attached-example-1
User Undermind
by
5.8k points

1 Answer

6 votes

Answer:

see below

Explanation:

You can determine the correct function by looking at the function and graph values at x = 1.

For some constant k, the function is ...

(g·h)(x) = g(x)·h(x) = (-3^x)(kx) = -kx·3^x

For x=1, the graph shows (g·h)(1) = 6. Using this in our expression for (g·h)(x), we have ...

(g·h)(1) = 6

-k(1)(3^1) = 6 . . . . use the expression for (g·h), filling in x=1

k = -2 . . . . . . . . . divide by -3

The function h(x) is ...

h(x) = -2x

Please help photo attached-example-1
User Dorin Rusu
by
5.9k points